The Roots of Pragmatic Thought in Al-Shatibi’s Maqasid-Oriented Jurisprudential Discourse - Sandid Mohammed Najib, Merni (El Omda in Linguistics and Discourse Analysis, 2019)
<section class="text-token-text-primary w-full focus:outline-none [–shadow-height:45px] has-data-writing-block:pointer-events-none has-data-writing-block:-mt-(–shadow-height) has-data-writing-block:pt-(–shadow-height) [&:has([data-writing-block])>*]:pointer-events-auto scroll-mt-[calc(var(–header-height)+min(200px,max(70px,20svh)))]" dir="auto" data-turn-id="request-WEB:32c27e8d-0406-4310-8c57-7cfb6e3aa634-14" data-testid="conversation-turn-30" data-scroll-anchor="true" data-turn="assistant"> <div class="text-base my-auto mx-auto pb-10 [–thread-content-margin:var(–thread-content-margin-xs,calc(var(–spacing)*4))] @w-sm/main:[–thread-content-margin:var(–thread-content-margin-sm,calc(var(–spacing)*6))] @w-lg/main:[–thread-content-margin:var(–thread-content-margin-lg,calc(var(–spacing)*16))] px-(–thread-content-margin)"> <div class="[–thread-content-max-width:40rem] @w-lg/main:[–thread-content-max-width:48rem] mx-auto max-w-(–thread-content-max-width) flex-1 group/turn-messages focus-visible:outline-hidden relative flex w-full min-w-0 flex-col agent-turn"> <div class="min-h-8 text-message relative flex w-full flex-col items-end gap-2 text-start break-words whitespace-normal outline-none keyboard-focused:focus-ring [.text-message+&]:mt-1" dir="auto" tabindex="0" data-message-author-role="assistant" data-message-id="9180cac6-2d1b-4bab-a8e3-c7bccf494895" data-message-model-slug="gpt-5-3" data-turn-start-message="true"> It may be observed that the primary sacred text—represented by the Noble Qur’an, revealed to the Prophet Muhammad (peace be upon him) in both wording and meaning—and the secondary sacred text—represented by the Prophetic Hadith, conveyed by the Prophet (peace be upon him) in the meaning intended by God Almighty, as the first Legislator, as affirmed in His saying: “It is nothing but revelation revealed”—and though the latter is considered a secondary source, it derives from the light of the former—together indicate that the foundation of legal rulings lies in a specific purpose inherent within them. This purpose explains the legal ruling as it is dispersed throughout the issue in its entirety, except in matters of the unseen, which belong exclusively to God Almighty. If this second element—the purpose behind the legal ruling—is absent, then the first cannot stand independently, and this constitutes a flaw on the part of the legal theorist who seeks to extract rulings, leading to distorted interpretation and unsound derivation.